The Effects of Perceived Benefits of Buy Now, Pay Later on the Spending Behavior of PLM Students Using the Shopee Platform - Domiquel, John Karl D., Esguerra, May Claire D., Madraso, Desiree S.J., Sefuentes, Rachelle Anne Z., Tan, Denize Mae R., Tan Franchesca M. 4 0 16; 5 (2023)
Abstract In this study, we explore how the perceived benefits of using the Buy Now, Pay Later (BNPL) feature impact the spending behavior of PLM students who are users of the Shopee platform. Our main objective is to examine how factors like enhanced affordability, convenience, and the ability to quickly obtain desired products influence the spending patterns of PLM students. The findings reveal that the perceived benefits of BNPL exert a significant impact on the spending behavior of PLM students. Students are attracted to the BNPL feature due to its perceived advantages, such as deferred payments, financial flexibility, and the ability to make purchases without immediate financial constraints. Consequently, PLM students exhibit higher purchase intentions and increased spending when utilizing the BNPL option on the Shopee platform. To gather data for this research, a quantitative research approach was employed, utilizing survey questionnaires as the main method of data collection. The participants in the study consisted of PLM students who actively participate in online shopping using the Shopee platform. Statistical methods such as Pearson product - correlation is applied to analyze the data collected from the surveys. The results shows that there is a minimal linear relationship between the Perceived benefits of BNPL in the spending behavior of the consumer. Customers are more likely to boost their spending if they believe Buy Now, Pay Later (BNPL) offers higher benefits.
Research Paper: (BSBA major in Financial management) - Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2